Kinetic ballooning modes as a constraint on plasma triangularity in commercial spherical tokamaks. (1st October 2022) - Davies, R; Dickinson, D; Wilson, H
Abstract: To be economically competitive, spherical tokamak (ST) power plant designs require a high β (plasma pressure/magnetic pressure) and sufficiently low turbulent transport to enable steady-state operation. A novel approach to tokamak optimisation is for the plasma to have negative triangularity, with experimental results indicating this reduces transport. However, negative triangularity is known to close access to the 'second stability' region for ballooning modes, and thus impose a hard β limit. Second stability access is particularly important in ST power plant design, and this raises the question as to whether negative triangularity is feasible. A linear gyrokinetic study of three hypothetical high β ST equilibria is performed, with similar size and fusion power in the range 500–800 MW. By closing the second stability window, the negative triangularity case becomes strongly unstable to long-wavelength kinetic ballooning modes (KBMs) across the plasma, likely driving unacceptably high transport. By contrast, positive triangularity can completely avoid the ideal ballooning unstable region whilst having reactor-relevant β, provided the on-axis safety factor is sufficiently high. Nevertheless, the dominant instability at long wavelength still appears to be the KBM, though it could be stabilised by flow shear.